That old feeling [videorecording (DVD)] - Reiner, Carl, 1922-2020-; Midler, Bette; Farina, Dennis, 1944-2013; Marshall, Paula (Universal Home Video, 1998)
Happily divorced for 14 years, Lilly and Dan still hate each other. But after a fight at their daughter's wedding, their hostility suddenly turns to unbridled passion.